Strategi Komunikasi Digital Marketing di Royal Konveksi Production (CV. Royal Putra Hutama) - Ciptaningrum, Alifya Diah Hayyu; Zuhriah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study aims to investigate the marketing communication strategies employed by Royal Konveksi & Production (CV. Royal Putra Hutama), a company in the garment and printing industry, with a primary focus on the use of social media, particularly Instagram. With the rapid growth of the garment industry in Indonesia, companies are increasingly competing to utilize effective marketing strategies to maintain their existence and business growth. The research method used is qualitative descriptive, involving in-depth analysis to understand the marketing communication strategies implemented by Royal Konveksi & Production (CV. Royal Putra Hutama). Data were collected through interviews with the company's owners and marketing staff, observation of their marketing activities on social media, and analysis of promotional content posted on the company's Instagram account. The results show that Royal Konveksi & Production (CV. Royal Putra Hutama) has successfully built a significant follower base on Instagram, reaching more than 11,000 followers in less than six years. They have also established business relationships with various leading companies. The marketing communication strategies they employ include careful planning with precise audience targeting, regular content scheduling, optimal utilization of Instagram features, presentation of engaging content, active interaction with followers, and creative and appealing promotions. Performance analysis and strategy adjustments are also integral parts of the company's efforts to ensure the effectiveness of their marketing campaigns. Thus, Royal Konveksi & Production (CV. Royal Putra Hutama) has effectively utilized Instagram as an effective marketing tool in the garment industry.